Mainstreaming biodiversity in business decisions: Taking stock of tools and gaps. (January 2023) - Katic, Pamela Giselle; Cerretelli, Stefania; Haggar, Jeremy; Santika, Truly; Walsh, Conor
Abstract: Most businesses depend on biodiversity, either directly, indirectly as ecosystem services, or through their supply chains. In negatively impacting biodiversity, businesses risk losing essential resources and services. As a result, it is important for the private sector to demonstrate strong and improved performance on biodiversity. This paper reviews and compares tools and approaches that help businesses measure their performance on biodiversity issues. Through a literature review and interviews of tool developers, we assess how tools are constructed, how they measure biodiversity performance, how and where they are being used by different businesses and how they contribute to achieving international targets for biodiversity. We found that tools perform a range of functions and are mostly applied at product, site, and supply chain level. Further efforts are needed to align tools with global biodiversity goals. Key knowledge gaps remain to better capture dependence on biodiversity and spatial spillover effects. Highlights: There is a rising demand for tools to include biodiversity in business decisions. To support biodiversity conservation, tools must be consistent and robust. We compare tools on how they support business in mainstreaming biodiversity. Tools can be leveraged to achieve real change in biodiversity performance.